Aquinas, Divine Simplicity, and Divine Freedom - Grant, W. Matthews (Proceedings of the American Catholic Philosophical Association, 2003)
Aquinas maintains that, although God created the universe, he could have created another or simply refrained from creating altogether. That Aquinas believes in divine free choice is uncontroversial. Yet doubts have been raised as to whether Thomas is entitled to this belief, given his claims concerning divine simplicity. According to simplicity, there is no potentiality in God, nor is there a distinction in God between God’s willing, His essence, and His necessary being. On the surface, it appears that these claims leave no room for divine free choice. I argue that attempts by Aquinas and a pair of his contemporary defenders to reconcile God’s freedom with God’s simplicity fail to resolve the problem. Nevertheless, I maintain that Aquinas provides the key to a resolution in his claim that while creatures are really related to God, God is not really related to creatures.